Using the combustion continuum to distinguish between explosive material and explosive article reactions for a unified scale in ordnance disposal categorization - Alford, Roland; Hazael, Rachael; Critchley, Richard (Taylor & Francis, 2025)
In this paper, we continue our exploration of the Combustion Continuum, building upon the foundational concepts and analyses presented in Part One of this two-part series (Alford, Hazael, and Critchley 2024). In the first paper, we introduced the benefit of considering burning, deflagration, and detonation (BDD) as lying on a continuum, defining the transition points from each regime to the next. This second paper builds on that background for a deeper understanding of how it can inform an understanding of how munitions react to explosive ordnance disposal (EOD) techniques designed specifically to prevent detonation of the explosive. We propose that when an explosive material within an explosive article (munition) detonates, the munition is said to high-order, but when the material burns or deflagrates, the munition low-orders. In short, a bomb explodes while the explosive within it detonates and low-orders when it deflagrates. This statement is explored in depth to form a robust justification for this and then propose a new munition reaction scale, based on physical evidence that allows results of EOD interventions to be correctly and consistently categorized.
Keywords: Chemical Physics; deflagration; detonation; UXO; explosive; high-order; low-order